Green roofs: an alternative for the reduction of surface runoff in the city of Recife, PE - Ribeiro de Holanda, Marco Aurélio Calixto; Soares, Willames de Albuquerque; Araújo de Souza, Alexandre da Câmara Lima; Corrêa de Oliveira, Diogo Botelho (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2021)
Constant flooding during periods of intense rain, aggravated by the impermeabilization of the soil, is a recurrent problem in many Brazilian cities, such as Recife, located in the state of Pernambuco. An efficient alternative that can mitigate this problem is the use of compensatory techniques such as green roofs. Adding a plant layer on the roof of buildings can serve to reduce atmospheric pollution, contribute to an improvement in thermal sensation, and absorb rainwater, reducing the intensity of flooding. Therefore, the objective was to evaluate the reduction in the volume of water drained from the surface in cities, through the implementation of green roofs. To carry out this evaluation, a green roof and a Pluviometer prototype were installed to collect data on the volume of water precipitated, drained, and absorbed by the prototypes. The results show that the volume of water drained by the green roofs can vary significantly, from over 100% down to complete absorption of the precipitation, i.e., 0% of the water volume, as occurred on some days in May, which is the month that presented the lowest rainfall of the analyzed period. In addition, the analyses also show that as well as the prototypes, the real green roof significantly reduces the flow of water from precipitation. The mean reduction of the total volume in the study was 50%, however, at longer intervals without precipitation, this reduction reached 78%. These results show that the impact of the implementation of compensatory techniques such as green roofs significantly reduces runoff, especially in a city that is flooded. Therefore, this study can serve as an incentive for public and private institutions to adopt the compensatory techniques of urban drainage for future or existing constructions, due to the aggregated social benefits, although they are not currently mandatory for all new constructions. The authors proposed the implementation of compensatory techniques, such as green roofs, in urban centers with high percentages of impermeable soil.